Design and implementation of buck-boost converter using Atmega 8535 microcontroller - Aslimeri; Anggraini, Widya; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2024)
To achieve the desired DC voltage, a variety of DC-DC converter types are employed, including buck converters, which can generate output voltages lower than the input voltage, boost converters, which can generate output voltages higher than the input voltage, and buck-boost converters, which can raise and lower the output voltage value based on the input voltage value. MOSFET is used in this study's buck-boost converter design because to its lower cost. The Pulse Widening Technique, commonly known as the Pulse Width Modulation (PWM) approach, is one way to control the MOSFET modulation pulse. In designing the buck-boost converter using the ATMega8535 microcontroller, it consists of several main components, namely: The ATMega8535 microcontroller functions as a PWM signal generator, the MOSFET gate drive consists of an optocoupler 4N25 IC, which is used for switching the IRFP 250N MOSFET. In this study, a buck-boost converter will be made that can increase and decrease DC voltage. The output voltage setting of the buck-boost converter can be done by adjusting the power switch modulation pulse used in the buck-boost converter. The test results of the buck-boost converter circuit show that the converter can work well to increase and decrease the voltage according to the desired set point. Both in testing the tool with different loads and constant voltage, the tool is able to work as desired